Multilevel mechanisms driving intraplate volcanism in Central Mongolia revealed by adjoint waveform tomography of receiver function and ambient noise data - Xu, Mijian (2025)
The genesis of the Cenozoic intraplate volcanism in Central Mongolia, characterized by sustained and low-volume eruptions remains debated due to the lack of a comprehensive model to interpret the Cenozoic volcanic activities. Here, we introduce a high-resolution 3D velocity model of the Hangay Dome, using a novel joint method which combines receiver function adjoint tomography and ambient noise adjoint tomography. The small-scale low-velocity zones in the crust and uppermost mantle reveal a crustal magma reservoir and partially molten subcontinental lithospheric mantle (SCLM). Melt fraction estimation indicates low-degree partially molten crust and SCLM. Combining previous geophysical and geochemical observations, we suggest that the volcanism in the Hangay Dome is driven by multilevel mechanisms. The remnant Mesozoic volatiles triggered upper mantle upwelling. This upwelling accumulated in the asthenosphere, heating the SCLM, and prompted its low-degree partial melting. The molten SCLM caused local lithospheric thinning and facilitated the magmatic underplating in the lower crust, eventually leading to the formation of the crustal magma reservoir.